2006
DOI: 10.1007/s00203-006-0176-7
|View full text |Cite
|
Sign up to set email alerts
|

A cryptic type I polyketide synthase (cpk) gene cluster in Streptomyces coelicolor A3(2)

Abstract: The chromosome of Streptomyces coelicolor A3(2), a model organism for the genus Streptomyces, contains a cryptic type I polyketide synthase (PKS) gene cluster which was revealed when the genome was sequenced. The ca. 54-kb cluster contains three large genes, cpkA, cpkB and cpkC, encoding the PKS subunits. In silico analysis showed that the synthase consists of a loading module, five extension modules and a unique reductase as a terminal domain instead of a typical thioesterase. All acyltransferase domains are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 54 publications
1
71
0
Order By: Relevance
“…For example, those produced by S. coelicolor include actinorhodin (Act [334]), undecylprodigiosin (Red [335]), calcium-dependent antibiotic (CDA [336]), and methylenomycin (Mmy [337]), the latter of which is carried on a plasmid. However, when the genome sequence of S. coelicolor was published (263), it became apparent that this species' true potential as a producer of natural products had actually been underestimated: over 20 biosynthetic gene clusters for secondary metabolites were identified (338), including one that appears to be for the production of a cryptic polyketide antibiotic (Cpk [339]). It rapidly became apparent that such "concealment" of antibioticproducing capabilities is the norm rather than the exception, with some streptomycetes harboring more than 50 different secondary metabolite gene clusters (340)(341)(342)(343).…”
Section: Streptomycetes As Antibiotic Factoriesmentioning
confidence: 99%
“…For example, those produced by S. coelicolor include actinorhodin (Act [334]), undecylprodigiosin (Red [335]), calcium-dependent antibiotic (CDA [336]), and methylenomycin (Mmy [337]), the latter of which is carried on a plasmid. However, when the genome sequence of S. coelicolor was published (263), it became apparent that this species' true potential as a producer of natural products had actually been underestimated: over 20 biosynthetic gene clusters for secondary metabolites were identified (338), including one that appears to be for the production of a cryptic polyketide antibiotic (Cpk [339]). It rapidly became apparent that such "concealment" of antibioticproducing capabilities is the norm rather than the exception, with some streptomycetes harboring more than 50 different secondary metabolite gene clusters (340)(341)(342)(343).…”
Section: Streptomycetes As Antibiotic Factoriesmentioning
confidence: 99%
“…One cluster was composed of STTGS_18_01720, STTGS_18_ 01730 and STTGS_18_ 01740. These three ORFs showed similarities to SCO6273, SCO6274 and SCO6275, respectively (Gottelt et al, 2010;Pawlik et al, 2007). However, the domain organizations of STTGS_ 18_ 01730 (KS/AT/ ACP) and SCO6274 (KS/ AT/ DH/ KR/ ACP-KS/ AT/ DH/ KR/ ACP) were quite different from each other, although those of STTGS_18_01720 and STTGS_18_01740 were identical to those of SCO6273 and SCO6275, respectively.…”
Section: Pks-i Gene Clustersmentioning
confidence: 90%
“…These include, a type III polyketide synthetase gene (SCO7221) involved in germicidin biosynthesis 34 activated following phosphate starvation, although PhoP has a limited effect. The same occurs to several cpk genes, 4,9 involved in biosynthesis of the polyketide coelimycin P1, 35 which includes an oxoacyl acyl carrier protein synthetase. Expression of the cpk cluster for coelimycin P1 biosynthesis is dependent of the phoP gene, 19 although Rodríguez-García et al 4 found that the cpk genes are transiently downregulated by PhoP.…”
Section: Phop Control Of Antibiotic and Other Secondary Metabolites Bmentioning
confidence: 91%